Pengaruh Kadar Air Optimum dengan Variasi Kepadatan terhadap Potensi dan Tekanan Mengembang pada Tanah Ekspansif - Bambang Pardoyo; Arif Hidayat (Department of Civil Engineering, Diponegoro University, 2012)
This research is purpose to know about the related between water content and compacted of expansive soil from potential swell and pressure swell. Water content is divided to seven part : OMC-15%, OMC-10%, OMC-5%, OMC, OMC+5%, OMC+10%, and OMC+15%.. Meanwhile the compacted is divided to amount of blow from each layer in standard mold of Proctor. An each layer is given 15x, 25x, 35x, and 55x blows. The result of the research is the try of high increased compaction so potential swell and pressure swell values will decrease. The value of the potential swell and pressure will decrease if the sample test condition to be more wet. Keywords: water content, expansive soilPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/2092[How to cite: Pardoyo, B. dan Hidayat, A., 2006, Pengaruh Kadar Air Optimum dengan Variasi Kepadatan terhadap Potensi dan Tekanan Mengembang pada Tanah Ekspansif, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 2, pp. 119-128]